2022
DOI: 10.6007/ijarped/v11-i1/12230
|View full text |Cite
|
Sign up to set email alerts
|

Trends on Technologies and Artificial Intelligence in Education for Personalized Learning: Systematic Literature Review

Abstract: The continuous development of new technology and rapid advancement of Artificial Intelligence (AI) contribute to the improvement and enrichment of the teaching and learning process. AI technology promotes a flexible, customized, and effective learning environment, as well as improves other educational competencies via personalized learning. To create a personalized learning environment, AI collects, compiles, and interprets data from a variety of sources to create student learning profiles. However, a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…This could include more sophisticated adaptive learning systems that dynamically adjust content and pacing based on real-time student performance (Elufioye, et. al., 2024, Hashim, et. al., 2022, Maghsudi, et.…”
Section: Future Directions and Implicationsmentioning
confidence: 99%
“…This could include more sophisticated adaptive learning systems that dynamically adjust content and pacing based on real-time student performance (Elufioye, et. al., 2024, Hashim, et. al., 2022, Maghsudi, et.…”
Section: Future Directions and Implicationsmentioning
confidence: 99%
“…For example, platforms like ALEKS and ASSISTments use AI algorithms to deliver adaptive assessments tailored to each student's learning needs. These platforms analyze students' responses to questions and adjust the difficulty level and content of subsequent questions based on their performance, ensuring that each student receives personalized feedback and support (Hashim, et. al., 2022, Lechuga & Doroudi, 2023, Moleka, 2023.…”
Section: Ai-driven Assessment and Feedbackmentioning
confidence: 99%
“…A large cluster of AIEd studies has focused on personalization for individual learners. In particular, the literature has shown that one of AI's major contributions is its capacity to assess individual students' performance (AlKhuzaey et al, 2021;González-Calatayud et al, 2021;Kurdi et al, 2020) and predict their learning outcomes (Arizmendi et al, 2022) for personalized learning (Bhutoria, 2022;Hashim et al, 2022). González-Calatayud et al (2021) reviewed 22 papers that demonstrated how educators used AI to assess learners.…”
Section: Artificial Intelligence In Education (Aied)mentioning
confidence: 99%